SUSTAINABLE DEVELOPMENT: CHALLENGES AND STRATEGIES IN SOUTH ASIA, SPOTLIGHTING PAKISTANI HIGHER EDUCATION - Zohaib Hassan Sain; Sitti Nurtina (Journal of Governance and Global Studies, 2024)
Examining Sustainable Development Goals (SDGs) across South Asian nations—Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka—reveals socio-economic and political challenges. Using World Bank, IMF, WHO, and FAO data, this study addresses complex hurdles hindering SDG achievement, focusing on poverty (SDG 1), health (SDG 3), education (SDG 4), and economic growth (SDG 8). The presented economic statistics underscore the urgent need for substantial measures. The study advocates for Developed Countries (DCs) to play a pivotal role, proposing at least one percent of GNP in development assistance. Success in SDG implementation requires good governance and structural reforms. The study promotes DC assistance to Under Developed Countries (UDCs), encouraging shared experiences to overcome challenges. The outcomes guide South Asian countries in crafting effective economic policies for SDG attainment by 2030. Additionally, exploring sustainability in Pakistani Higher Education Institutions, the research reviews 26 HEC-published studies. Synthesizing these studies uncovers progress and challenges in achieving Education for Sustainable Development (ESD). Stakeholders, including administrators, leaders, teachers, and students, contribute to the transformative process. The analysis emphasizes governance, communication, coordination, campus outreach, and addresses challenges. Emphasizing logistical support and quality education (SDG 4) aligns with SDGs. The study serves as a guide for educators, policymakers, and curriculum developers to foster Sustainable Development, aiding researchers in framing questions for sustainable development goals.